Optimasi Proses Mikroenkapsulasi Minyak Kelapa Murni dengan Bahan Penyalut β-Cyclodextrin - Sapatra, Enrico Fendy; Paramita, Vita (METANA, 2021)
Virgin Coconut Oil (VCO) atau biasa kita kenal dengan minyak kelapa murni memiliki banyak sekali manfaat bagi kesehatan manusia. Selain bagus untuk kesehatan kulit, mengonsumsi VCO dapat mencegah dan mengobati penyakit diabetes. Namun terdapat permasalahan dari segi rasa dan tingkat kestabilan ketika harus mengonsumsi VCO secara langsung. Maka dari itu dibutuhkan proses lanjutan berupa pembentukan kompleks inklusi dari minyak kelapa itu sendiri melalui proses mikroenkapsulasi menggunakan spray drying. Bahan penyalut yang digunakan dalam proses mikroenkapsulasi ini adalah β-siklodekstrin.  Minyak kelapa murni akan tersalutkan dalam β-siklodekstrin melalui proses film forming. Dalam spray drying variabel bebas untuk optimasi proses yang dilakukan adalah suhu (80°C, 100°C, 120 °C), laju alir (8mL/menit, 10 mL/menit, 12 mL/menit), dan perbandingan jumlah bahan antara β-cyclodekstrin:VCO (1:1, 1,5:1, dan 2:1). Berdasarkan hasil yang diperoleh, massa produk tertinggi dari proses mikroenkapsulasi di spray drying diperoleh dengan kondisi operasi suhu 100°C, laju alir 10 mL/menit, dan perbandingan antara β-cyclodextrin : VCO adalah sebesar 2,0. A Virgin Coconut Oil (VCO) or usually known as virgin coconut oil has many benefits for human health. Besides being good for skin health, consuming VCO can prevent and treat diabetes. However, there are problems in terms of taste and level of stability when it comes to consuming VCO directly. Therefore, a further process is needed in the form of the formation of an inclusion complex from coconut oil itself through a microencapsulation process using spray drying. The coating material used in this microencapsulation process is β-cyclodextrin. In spray drying, the independent variables for process optimization are temperature (80°C, 100°C, 120°C), flow rate (8mL/min, 10 mL/min, 12 mL/min), and the ratio of the number of ingredients between β -cyclodextrins: VCO (1: 1, 1,5: 1, and 2: 1). Based on the results obtained, the highest product mass from the microencapsulation process in spray drying was obtained under operating conditions with a temperature of 100° C, a flow rate of 10 mL/min, and the ratio between β-cyclodextrin: VCO is 2:1. maximum 200 word abstract in English in italics with Times New Roman 11 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief.